2015
DOI: 10.1074/jbc.m115.666883
|View full text |Cite|
|
Sign up to set email alerts
|

Regulation of Plasma Membrane Localization of the Na+-Taurocholate Cotransporting Polypeptide (Ntcp) by Hyperosmolarity and Tauroursodeoxycholate

Abstract: Background:Little is known about the effect of hyperosmotic hepatocyte shrinkage on Na ϩ -taurocholate cotransporting

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
27
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(35 citation statements)
references
References 79 publications
8
27
0
Order By: Relevance
“…This is due to a TUDCinduced RGD peptide-sensitive generation of cyclic adenosine monophosphate (cAMP) [25] . In line with this, like TUDC cAMP also prevents hyperosmotic Fyn activation [26,27] .…”
Section: Mapksupporting
confidence: 66%
See 3 more Smart Citations
“…This is due to a TUDCinduced RGD peptide-sensitive generation of cyclic adenosine monophosphate (cAMP) [25] . In line with this, like TUDC cAMP also prevents hyperosmotic Fyn activation [26,27] .…”
Section: Mapksupporting
confidence: 66%
“…1 ). As also shown in figure 1 , perfusion of the rat liver with hyperosmotic medium results in Bsep retrieval from the canalicular membrane, and this effect can completely be reversed by TUDC, which leads to Bsep re-insertion [26,27] . This process is sensitive to the RGD peptide [26,27] .…”
Section: Mapkmentioning
confidence: 69%
See 2 more Smart Citations
“…The high sensitivity of intracellular bile acid concentration to BSEP activity as shown in our model and in the DILIsym model can explain the large variation in sensitivity for cholestatic drug effects in the human population. The value found for NTCP of 5.9 fmol/μg plasma membrane protein might have been an overestimation of active transporter as it is higher than found by others (Qiu et al, 2013;Wang et al, 2015) and it has been reported that the transporter can be also found in submembrane vesicles (Sommerfeld et al, 2015;Webster et al, 2002). The role of OATPs in the uptake of bile acids was assumed to be low, but this should be incorporated in a future version of the model.…”
Section: S Notenboom Et Almentioning
confidence: 82%